From simple questions to complex issues, IDNLearn.com has the answers you need. Our platform provides prompt, accurate answers from experts ready to assist you with any question you may have.
Sagot :
Certainly! Let's go through each part of this question step-by-step.
---
### Part 1: Finding the Equation of the Plane
We need to find the equation of the plane passing through points [tex]\( P(0,0,1) \)[/tex], [tex]\( Q(2,0,0) \)[/tex], and [tex]\( R(0,3,0) \)[/tex].
1. Find two vectors in the plane:
- Vector [tex]\( \mathbf{PQ} \)[/tex] going from [tex]\( P \)[/tex] to [tex]\( Q \)[/tex]:
[tex]\[ \mathbf{PQ} = \mathbf{Q} - \mathbf{P} = (2,0,0) - (0,0,1) = (2,0,-1) \][/tex]
- Vector [tex]\( \mathbf{PR} \)[/tex] going from [tex]\( P \)[/tex] to [tex]\( R \)[/tex]:
[tex]\[ \mathbf{PR} = \mathbf{R} - \mathbf{P} = (0,3,0) - (0,0,1) = (0,3,-1) \][/tex]
2. Find the normal vector to the plane by taking the cross product of [tex]\( \mathbf{PQ} \)[/tex] and [tex]\( \mathbf{PR} \)[/tex]:
[tex]\[ \mathbf{n} = \mathbf{PQ} \times \mathbf{PR} = \begin{vmatrix} \mathbf{i} & \mathbf{j} & \mathbf{k} \\ 2 & 0 & -1 \\ 0 & 3 & -1 \\ \end{vmatrix} = \mathbf{i} (0 \cdot (-1) - 3 \cdot (-1)) - \mathbf{j} (2 \cdot (-1) - 0 \cdot (-1)) + \mathbf{k} (2 \cdot 3 - 0 \cdot 0) \][/tex]
Simplifying this, we get:
[tex]\[ \mathbf{n} = (0 + 3)\mathbf{i} + (2)\mathbf{j} + (6)\mathbf{k} = 3\mathbf{i} + 2\mathbf{j} + 6\mathbf{k} = (3,2,6) \][/tex]
3. Form the equation of the plane:
The equation of a plane is given by:
[tex]\[ a x + b y + c z = d \][/tex]
where [tex]\( (a, b, c) \)[/tex] is the normal vector [tex]\( \mathbf{n} \)[/tex]. Using the normal vector [tex]\( (3,2,6) \)[/tex]:
[tex]\[ 3x + 2y + 6z = d \][/tex]
4. Find the constant [tex]\(d\)[/tex] by substituting one of the points on the plane, say [tex]\( P(0,0,1) \)[/tex], into the plane equation:
[tex]\[ 3(0) + 2(0) + 6(1) = d \implies 6 = d \][/tex]
Thus, the equation of the plane is:
[tex]\[ 3x + 2y + 6z = 6 \][/tex]
---
### Part 2: Proof by Mathematical Induction
We need to prove that if [tex]\( B \)[/tex] is a square matrix such that [tex]\( B(B-1)=0 \)[/tex], then [tex]\( (I+B)^n-I=(-1+2^n) B \)[/tex], where [tex]\( I \)[/tex] is the identity matrix of the same size as [tex]\( B \)[/tex].
#### Base Case (n = 1):
For [tex]\( n=1 \)[/tex]:
[tex]\[ (I+B)^1 - I = I + B - I = B \\ (-1 + 2^1)B = B \\ \) This satisfies the base case. #### Inductive Step: Assume that the statement holds for \( n = k \). That is: \[ (I+B)^k - I = (-1 + 2^k) B \][/tex]
We need to prove that the statement holds for [tex]\( n = k+1 \)[/tex]. Consider [tex]\( (I+B)^{k+1} \)[/tex]:
[tex]\[ (I+B)^{k+1} = (I+B)^k (I+B) \][/tex]
By the inductive hypothesis:
[tex]\[ (I+B)^k = I + (-1+2^k) B \rightarrow \text{Let this be } X \][/tex]
Then:
[tex]\[ (I + B)^{k+1} = (I + (-1 + 2^k) B) (I + B) = I + B + (-1 + 2^k) B + (-1 + 2^k) B^2 \][/tex]
Using the property [tex]\( B(B-1)=0 \)[/tex]:
[tex]\[ B^2 = B \][/tex]
So:
[tex]\[ (I + B)^{k+1} - I = B + (-1 + 2^k) B + (-1 + 2^k) B = B + (-1 + 2^k) B + (-1 + 2^k) B \][/tex]
Simplify and combine similar terms:
[tex]\[ B + (-1 + 2^k) B + (-1 + 2^k) B = B + (-1 + 2^k + 2^k) B = B + (2 \times 2^k - 1) B = B + (2^{k+1} - 1) B = (-1 + 2^{k+1}) B \][/tex]
Thus, the inductive step is proven and hence, the statement is true for all [tex]\( n \geq 1 \)[/tex]:
[tex]\[ (I+B)^n - I = (-1 + 2^n) B \][/tex]
This completes the proof using mathematical induction.
---
### Part 1: Finding the Equation of the Plane
We need to find the equation of the plane passing through points [tex]\( P(0,0,1) \)[/tex], [tex]\( Q(2,0,0) \)[/tex], and [tex]\( R(0,3,0) \)[/tex].
1. Find two vectors in the plane:
- Vector [tex]\( \mathbf{PQ} \)[/tex] going from [tex]\( P \)[/tex] to [tex]\( Q \)[/tex]:
[tex]\[ \mathbf{PQ} = \mathbf{Q} - \mathbf{P} = (2,0,0) - (0,0,1) = (2,0,-1) \][/tex]
- Vector [tex]\( \mathbf{PR} \)[/tex] going from [tex]\( P \)[/tex] to [tex]\( R \)[/tex]:
[tex]\[ \mathbf{PR} = \mathbf{R} - \mathbf{P} = (0,3,0) - (0,0,1) = (0,3,-1) \][/tex]
2. Find the normal vector to the plane by taking the cross product of [tex]\( \mathbf{PQ} \)[/tex] and [tex]\( \mathbf{PR} \)[/tex]:
[tex]\[ \mathbf{n} = \mathbf{PQ} \times \mathbf{PR} = \begin{vmatrix} \mathbf{i} & \mathbf{j} & \mathbf{k} \\ 2 & 0 & -1 \\ 0 & 3 & -1 \\ \end{vmatrix} = \mathbf{i} (0 \cdot (-1) - 3 \cdot (-1)) - \mathbf{j} (2 \cdot (-1) - 0 \cdot (-1)) + \mathbf{k} (2 \cdot 3 - 0 \cdot 0) \][/tex]
Simplifying this, we get:
[tex]\[ \mathbf{n} = (0 + 3)\mathbf{i} + (2)\mathbf{j} + (6)\mathbf{k} = 3\mathbf{i} + 2\mathbf{j} + 6\mathbf{k} = (3,2,6) \][/tex]
3. Form the equation of the plane:
The equation of a plane is given by:
[tex]\[ a x + b y + c z = d \][/tex]
where [tex]\( (a, b, c) \)[/tex] is the normal vector [tex]\( \mathbf{n} \)[/tex]. Using the normal vector [tex]\( (3,2,6) \)[/tex]:
[tex]\[ 3x + 2y + 6z = d \][/tex]
4. Find the constant [tex]\(d\)[/tex] by substituting one of the points on the plane, say [tex]\( P(0,0,1) \)[/tex], into the plane equation:
[tex]\[ 3(0) + 2(0) + 6(1) = d \implies 6 = d \][/tex]
Thus, the equation of the plane is:
[tex]\[ 3x + 2y + 6z = 6 \][/tex]
---
### Part 2: Proof by Mathematical Induction
We need to prove that if [tex]\( B \)[/tex] is a square matrix such that [tex]\( B(B-1)=0 \)[/tex], then [tex]\( (I+B)^n-I=(-1+2^n) B \)[/tex], where [tex]\( I \)[/tex] is the identity matrix of the same size as [tex]\( B \)[/tex].
#### Base Case (n = 1):
For [tex]\( n=1 \)[/tex]:
[tex]\[ (I+B)^1 - I = I + B - I = B \\ (-1 + 2^1)B = B \\ \) This satisfies the base case. #### Inductive Step: Assume that the statement holds for \( n = k \). That is: \[ (I+B)^k - I = (-1 + 2^k) B \][/tex]
We need to prove that the statement holds for [tex]\( n = k+1 \)[/tex]. Consider [tex]\( (I+B)^{k+1} \)[/tex]:
[tex]\[ (I+B)^{k+1} = (I+B)^k (I+B) \][/tex]
By the inductive hypothesis:
[tex]\[ (I+B)^k = I + (-1+2^k) B \rightarrow \text{Let this be } X \][/tex]
Then:
[tex]\[ (I + B)^{k+1} = (I + (-1 + 2^k) B) (I + B) = I + B + (-1 + 2^k) B + (-1 + 2^k) B^2 \][/tex]
Using the property [tex]\( B(B-1)=0 \)[/tex]:
[tex]\[ B^2 = B \][/tex]
So:
[tex]\[ (I + B)^{k+1} - I = B + (-1 + 2^k) B + (-1 + 2^k) B = B + (-1 + 2^k) B + (-1 + 2^k) B \][/tex]
Simplify and combine similar terms:
[tex]\[ B + (-1 + 2^k) B + (-1 + 2^k) B = B + (-1 + 2^k + 2^k) B = B + (2 \times 2^k - 1) B = B + (2^{k+1} - 1) B = (-1 + 2^{k+1}) B \][/tex]
Thus, the inductive step is proven and hence, the statement is true for all [tex]\( n \geq 1 \)[/tex]:
[tex]\[ (I+B)^n - I = (-1 + 2^n) B \][/tex]
This completes the proof using mathematical induction.
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your questions deserve precise answers. Thank you for visiting IDNLearn.com, and see you again soon for more helpful information.